Harzianopyridone Supplementation Reduced Chromium Uptake and Enhanced Activity of Antioxidant Enzymes in Vigna radiata Seedlings Exposed to Chromium Toxicity - Shah, Anis Ali; Shah, Adnan Noor; Bilal Tahir, Muhammad; Abbas, Asad; Javad, Sumera; Ali, Sajid; Rizwan, Muhammad; Alotaibi, Saqer S.; Kalaji, Hazem M.; Telesinski, Arkadiusz; Javed, Talha; AbdElgawad, Hamada (Frontiers in Plant Science, 2022)
This is the first study that explains the role of harzianopyridone (HZRP) in alleviation of chromium (Cr) stress alleviation in Vigna radiata (L.). Current research revealed that supplementation of harzianopyridone alleviates Cr stress in V. radiata. V. ragiata seedlings were exposed to 50 mg kg-1 Cr for 30 days. Cr stress reduced growth, chlorophyll (Chl) content, net photosynthetic rate, gas-exchange attributes along with enhanced electrolyte leakage (EL), hydrogen peroxide (H2O2) and lipid peroxidation (MDA). Application of HZRP enhanced intercellular CO2 concentration, stomatal conductance and net photosynthetic rate with decreased activity of chlorophyllase in V. radiata seedlings exposed to Cr stressed conditions. Our research showed that HZRP increased the activity of antioxidative enzymes i.e., superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) activity in V. radiata seedlings grown in normal and Cr-polluted potted soil. In addition to this, total phenolic and flavonoids content was also incremented in plants grown in Cr-contaminated soil. It is proposed that further research can be conducted to evaluated the potential of HZRP in mitigation of abiotic stresses in plants.